Análise histopatológica e imuno-histoquímica da erupção papular prurítica associada ao vírus da imunodeficiência humana - Tozzi, Brunela Bastos (2012)
Introduction: Papular pruritic eruption (PPE) is characterized by the presence of pruritic erythematous papules as chronic disease that affects oftenly seropositive patients. The lesions are seen in different stages, preferably in the trunk and extremities, and end with post inflammatory hyperpigmentation and / or scars resulting from scratching. Objectives: To evaluate the hitopathological and immunohistochemical features of the PPE. Methods: The study enrolled HIV-positive patients with clinical diagnosis of PPE carried out at University Hospital Cassiano Antonio Moraes of the Federal University of Espirito Santo in Vitória, ES. Patients were dermatological examinated and skin lesions photographed. Skin biopsies were obtained to evaluate the histopathological and immunohistochemical features. Results: Thirty-nine patients with EPP were biopsied, 17 were women and 22 men, mean age was 40.2 years ranging from 25 to 63 years. Among the histopathological biopsies, 6 patterns were found and these often: 1) dermal perivascular inflammatory infiltrate, 2) inflammatory infiltrate affecting the follicular unit; 3) interstitial inflammatory infiltrate, 4) inflammatory infiltrate in the subcutaneous tissue, 5) inflammatory infiltrate affecting at least one nerve, 6) signal of the scratching in the epidermis. About immunohistochemistry features, Langerhans cells are found in normal amounts in the epidermis and relatively increased in dermal inflammatory infiltrate. There are predominantly CD8 + T lymphocyte and macrophages in the inflammatory infiltrate compared with CD4 + T lymphocytes. No microorganisms were found using the Ziehl-Neelsen staining and Grocott. Conclusions: It was identified six patterns present in biopsy, in order to obtain a set of histopathologic and immunohistochemical to describe and characterize the PPE histopathological diagnosis. The dermal perivascular inflammatory infiltrate is essential for diagnosis, and other tissue alterations are not mandatory that may be present together or separately, at different stages of the skin lesions.